PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN, DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DI KANTOR PELAYANAN PAJAK PRATAMA MEDAN PETISAH - Ginting, Kiki Lala Rosi; Sianturi, Marudut; Matondang, Sofiyan (JURNAL PROINTEGRITA, 2020)
This study aims at finding the influence of organizational culture, leadership, and compensation segmentally and simultaneously on employee performance at KPP Pratama Medan Petisah. The population of this research is 105 employees working as staff employees (outside the Head of Office and Head of Section). The number of samples taken is 83 people using Probability Sampling with the Proportionate Stratified Random Sampling method. Data collection is using questionnaires, interviews, and documentation study while the data analysis technique used is the classical assumption test, multiple regressions, t test, F test, and the coefficient of determination. It is found that the better the organizational culture, the higher the performance; the better the leadership, the higher the performance; the better the employee compensation, the higher the performance. The variables of organizational culture, leadership, and compensation simultaneously have a significant effect on employee performance variables. The coefficient of determination Adjust R2 is 0.975. This means that variations in employee performance can be explained by organizational culture, leadership, and compensation of 97.5%, while the remaining 2.5% is explained by other factors such as training, work discipline, and other factors.